2002
DOI: 10.4319/lo.2002.47.6.1790
|View full text |Cite
|
Sign up to set email alerts
|

Interactive aggregation and sedimentation of diatoms and clay‐sized lithogenic material

Abstract: Monospecific diatom cultures (Thalassiosira punctigera and Skeletonema costatum) were incubated in rotating cylinders together with clay suspensions, present in a range of concentrations (5-100 mg kaolinite L Ϫ1) and as different minerals (50 mg L Ϫ1 kaolinite, smectite, illite, and clay-sized quartz powder). The addition of lithogenic suspensions to diatom cultures accelerated the formation of visible aggregates in the roller tanks by a factor of Ͼ3. Aggregate size decreased and density increased proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
84
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 30 publications
12
84
1
1
Order By: Relevance
“…In our main experiment here, illite helped to drive coagulation, measured as total area of aggregated material or as aggregate number, which was highly significantly positively correlated with illite concentration (n 5 14, p 5 0.0005). That the concentration of illite would affect the size and number as well as characteristics of aggregates was expected from previous experiments (Hamm 2002;Passow and De La Rocha 2006).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In our main experiment here, illite helped to drive coagulation, measured as total area of aggregated material or as aggregate number, which was highly significantly positively correlated with illite concentration (n 5 14, p 5 0.0005). That the concentration of illite would affect the size and number as well as characteristics of aggregates was expected from previous experiments (Hamm 2002;Passow and De La Rocha 2006).…”
Section: Discussionmentioning
confidence: 88%
“…The relatively lower TEP content (Engel and Schartau 1999;Azetsu-Scott and Passow 2004) and the higher illite content (Ploug et al 2008a,b;Fischer and Karakas 2009;Iversen and Ploug 2010) of the aggregates formed at high initial suspended concentrations of illite should have increased excess density and hence sinking velocity of aggregates in the high-clay treatments. But incorporation of minerals also reduces the size of aggregates (Passow and De La Rocha 2006;De La Rocha et al 2008), which diminishes sinking velocity (McCave 1975;Hamm 2002;De La Rocha and Passow 2007). In previous experiments, the increase in sinking speed related to additional excess density has generally predominated over the loss of sinking speed due to loss of size, but the overall outcome of mineral addition in a given situation will certainly vary with a number of factors (the size, density, and charge of the minerals, the composition and character of the organic matter, the relative and absolute concentrations of the minerals and the organic matter, and so forth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of diatom aggregates mixed with minerals, e.g., clays and carbonate, have demonstrated that, on average, these aggregates are smaller than those formed in pure diatom cultures (Hamm, 2002;Passow and De La Rocha, 2006). In those studies, however, sinking velocity was not directly measured, but applying Stoke's law it was argued that the smaller size of mixed aggregates may lead to lower sinking velocities despite their higher content of ballasting minerals as compared to those composed of diatoms, only.…”
Section: Discussionmentioning
confidence: 99%
“…off NW Africa, the role of dust as ballast should be considered. However, laboratory experiments have shown that lithogenic material could even decrease the downward flux of phytoplankton biomass (Hamm, 2002). According to Berelson (2002), particle sinking rates estimated from sediment trap studies are not controlled by the lithogenic contents of particles.…”
Section: Introductionmentioning
confidence: 99%